Determination of proximate and mineral contents of chocolate cupcakes prepared with persea americana fruit as fat replacer - Shamsudin, Nur Izzati Mohd (Universiti Sains Malaysia, 2015)
Replacing fat in baked products with fruit based ingredients can aid in the overall reduction of fat intake and increase the consumption of fruits. Avocado (Persea americana) fruits contain high monounsaturated fat and various phytochemicals such as carotenoids and phenolics. Consumption of cupcakes has been has been increasing and becoming a trend since the past few years. Thus, there is an opportunity to better increase the nutritional quality of cupcake to better improve the nutritional status of community. Thus, a study was conducted to determine the macronutrients and mineral contents of chocolate cupcake prepared by with avocado puree as butter replacer. Chocolate cupcakes were prepared by using pureed avocado (0%, 25 %, 50%, and 75%) in place of butter. Proximate analysis was determined by using standard AOAC method. Mineral content was determined by using atomic absorption spectrophotometry. The results were analyzed by using SPSS (version 21.0) software. The results show that the mean values of moisture, protein and fat contents were significantly different (P 0.05) among the four samples. The moisture increased significantly (P < 0.05) with the increase in percentage of avocado puree. The highest protein content was found in 75% fat-replaced sample (10.87 g/lOOg) while the control sample (9.19 g/100g) contained the lowest protein. As the percentage of avocado increased, the fat content was significantly decreased (P 0.05) in all fat-replaced samples. The 75% fat-replaced sample (8.33 g/100g) contained 63% less fat than the control sample (22.74 g/100g). There was no significance different in the ash and carbohydrate values. The mineral contents show that sodium, potassium, magnesium and zinc were highest in the 25% fat-replaced sample. As a conclusion, the production of chocolate cupcakes prepared with avocado puree as fat replacer enhanced its nutritional composition with the increase in protein and minerals and decrease in fat content.